Characteristics Of Effluent Wastewater In Hospital (In Literature Review) - Zairinayati; Chun Hoe Tan; Norhashima Abd Rashid (Jurnal Inspirasi Kesehatan, 2023)
Background: Waste from medical and non-medical activities can be generated by hospital health service operations in both solid and liquid forms. Hospital liquid waste is waste that endangers the environmental ecosystem and human health around the hospital and even the wider environment. The purpose of this study was to determine the value of wastewater effluent after treatment which includes BOD, COD, TSS in wastewater from various hospitals. Method: This study is a literature review study. Searching for articles using the published or perish application is continued, followed by database searches on Scopus, Google Scholar, Semantic Scholar, published in 2018-2023. 69 articles found were then selected into 5 articles. Results and Discussion: based on the 5 reviewed research articles it was found that the average values ​​​​for the chemical parameters of hospital wastewater from various hospitals in several countries showed that the BOD, COD, TSS parameters exceeded waste disposal standards, besides that other hazardous substances were detected, including the use of other disinfectants used in large quantities in health care facilities, a significant level of pollution was shown from the surgical section which was almost two to four times higher than other sections, this caused high chemical contamination contained in hospital wastewater. Conclusion: the characteristics of hospital wastewater show different values ​​between countries. This depends on the type of material, origin of various wastes, region, frequency of detection and quantification of these compounds. Therefore